Method for preparing molybdenum-copper composite board based on freeze drying method

The freeze-drying method was used to prepare molybdenum-copper composite plates, which solved the problems of formability and density of MoCu composite materials, realized the efficient utilization and performance improvement of materials, and promoted industrial production.

CN119304177AInactive Publication Date: 2025-01-14XINZHOU SHANGHUAYANG ELECTRICAL EQUIP CO LTD

Patent Information

Application Number
CN202411868985.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for preparing MoCu composite materials suffer from poor formability, uneven two-phase distribution, and difficulty in achieving density. Furthermore, the material utilization rate is low, resulting in the inability to fully realize the desired performance.

Method used

Molybdenum-copper composite plates were prepared by freeze-drying. The molybdenum skeleton was formed by slurry preparation, freeze-drying, vacuum debinding and pre-sintering. Combined with melt infiltration sintering technology, the pore structure and two-phase distribution were controlled to form interconnected pores to improve density and uniformity.

Benefits of technology

This improved the density and conductivity of molybdenum-copper composite plates, reduced material loss, lowered manufacturing costs, and promoted the industrial production of high-performance molybdenum-copper composite plates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119304177A_ABST
    Figure CN119304177A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of molybdenum-copper composite board preparation, in particular to a method for preparing a molybdenum-copper composite board based on a freeze-drying method, which comprises the following steps: preparation of slurry, preparation of a molybdenum skeleton, determination of a copper block, infiltration sintering and post-treatment. According to the method, the problem that two phases of an existing molybdenum-copper composite material are distributed unevenly is effectively solved, the density of the molybdenum-copper composite material is improved, the molybdenum-copper composite material has excellent conductivity, the freeze drying cost is low, and industrial production of the high-performance molybdenum-copper composite plate can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of molybdenum-copper composite plates, and in particular to a method for preparing a molybdenum-copper composite plate based on a freeze-drying method. Background Art

[0002] With the rapid development of electronic power technology in recent years, the integration of integrated circuits has also increased. At present, the wiring width of integrated circuits has reached 3 nanometers. The increase in integration can undoubtedly reduce the size of electronic products and improve chip computing power. However, while improving the performance, the direct problem is that the heat dissipation of electronic products during use increases sharply, and the heat dissipation space continues to decrease, causing the product to freeze or even fail due to high temperature. This puts higher requirements on the heat dissipation performance of electronic products. As the core of electronic product heat dissipation, electronic packaging materials play a decisive role in the heat dissipation process of electronic products. High-performance electronic packaging heat dissipation materials have also become the key to solving the above problems.

[0003] MoCu composite material is only a "pseudo alloy" formed by Mo and Cu phases, which has the excellent properties of these two metal materials, with a low and controllable thermal expansion coefficient and excellent thermoelectric properties. Therefore, the organization and performance of MoCu composite materials can be regulated based on composite powder raw material design, preparation process regulation, static pressing, mechanical rolling and other processing processes to achieve the optimization of MoCu composite material performance. At present, the powder metallurgy method is mainly used to prepare MoCu composite materials at home and abroad. However, the MoCu composite materials prepared by powder metallurgy have problems such as poor formability, uneven distribution of two phases, and difficulty in complete densification, which greatly limits the excellent performance of MoCu composite materials during the reaction process. Therefore, it is urgent to seek a new MoCu composite material preparation technology to obtain a highly dense MoCu composite material and give full play to the excellent performance of MoCu composite materials.

[0004] MoCu composite materials are often put into use in the form of plates. Therefore, after the composite materials are prepared by traditional processes, the materials often need to be rolled. During the rolling process, the materials need to be cut and the ends deformed and trimmed. The material loss rate is about 30%~40%. How to reduce material loss and achieve efficient utilization of composite materials is also a key technical issue. Summary of the invention

[0005] In view of the above problems, the present invention provides a method for preparing molybdenum-copper composite plates based on freeze-drying, which not only effectively solves the problem of uneven distribution of two phases in existing molybdenum-copper composite plates and improves the density of molybdenum-copper composite plates, but also reduces material loss and reduces the preparation cost of molybdenum-copper composite plates, thereby promoting the industrial production of high-performance molybdenum-copper composite plates.

[0006] To achieve the above object, the technical solution of the present invention is as follows: A method for preparing a molybdenum-copper composite plate based on a freeze-drying method comprises the following steps: S1. Preparation of slurry: mixing a dispersant, a binder, molybdenum powder, copper powder and deionized water to obtain a mixed solution; stirring the mixed solution with a magnetic stirrer to obtain a slurry precursor; then transferring the slurry precursor into a stainless steel ball mill, and dispersing it with a planetary ball mill to obtain the desired slurry; S2, preparation of a molybdenum skeleton, transferring the slurry obtained in step S1 into a freezing mold, freezing and drying the slurry using a freeze dryer to obtain a molybdenum skeleton green body; and then debinding and pre-sintering the molybdenum skeleton green body using a vacuum tube furnace to obtain a molybdenum skeleton; S3, preparation of copper block, using pure copper plate, cutting it, and cleaning and sandblasting its surface to obtain the required copper block; S4, infiltration sintering, placing the molybdenum skeleton prepared in step S2 in a sintering mold, placing the copper block prepared in step S3 on the molybdenum skeleton, and performing infiltration sintering in a sintering furnace, wherein the copper block infiltrates into the molybdenum skeleton through infiltration to obtain a molybdenum-copper composite plate; S5, post-processing, firstly, the molybdenum-copper composite plate obtained in step S4 is milled to remove the excess copper on the surface, then shaped on a press, and finally ground to form a final product.

[0007] As a further scheme of the present invention: in step S1, the solid content of molybdenum powder in the slurry is 50~80 vol%, the solid content of copper powder is 5~35 vol%, the particle size of the molybdenum powder is 5~10 μm, and the particle size of the copper powder is 3~5 μm; the dispersant is sodium polyacrylate, and the concentration of the sodium polyacrylate is 0.004~0.01 g / ml; the binder is xanthan gum, and the concentration of the xanthan gum is 0.004~0.012 g / ml.

[0008] As a further solution of the present invention: in step S1, the rotation speed of the magnetic stirrer is 100-200 r / min, and the stirring time is 45 min-1 h; the diameter of the stainless steel ball mill is 2-5 mm, and the ball-to-material ratio is 3:1; the rotation speed of the planetary ball mill is 200-300 r / min, and the dispersion time is 10-12 h, and the viscosity of the obtained slurry is 4000-5000 mPa·s.

[0009] As a further solution of the present invention: in step S2, the freezing mold includes an insulating tube body and a cold transfer bottom plate, the bottom of the insulating tube body is fixedly connected to the cold transfer bottom plate, the height of the insulating tube body is ≤ 1 mm, the insulating tube body is made of acrylic insulating tube material, and the cold transfer bottom plate is made of copper plate.

[0010] As a further solution of the present invention: in step S2, the cooling temperature of the freeze dryer is -50 ~ -70 ° C, the cooling time is 3 ~ 4 h, the drying temperature is -15 ~ -20 ° C, and the drying time is 24 ~ 48 h; the heating rate of the vacuum tube furnace is 5 ~ 8 ° C / min, and when the temperature is raised to 400 ~ 450 ° C, it is kept warm for 1 ~ 2 h; the debinding and pre-sintering processes are both carried out in a hydrogen atmosphere, and the gas flow rate of the hydrogen is 50 ~ 80 sccm.

[0011] As a further solution of the present invention: the copper infiltrated into the molybdenum skeleton by the copper block is called infiltration copper, the copper in the molybdenum-copper composite plate is composed of the copper added in step S1 and the infiltration copper, and the mass fraction of the infiltration copper is w 铜2 =100%-w 钼 -w 铜1 , where w 钼 is the mass fraction of the molybdenum powder added in step S1 in the molybdenum-copper composite plate, w 铜1 is the mass fraction of the copper powder added in step S1 in the molybdenum-copper composite plate. The mass of the infiltrated copper is calculated according to the mass of the prepared molybdenum-copper composite plate. In step S3, the mass of the copper block is 1.2 times the mass of the infiltrated copper.

[0012] As a further solution of the present invention: in step S4, the sintering mold is made of graphite or corundum material, the heating rate of the sintering furnace is 5~8 ℃ / min, and when the temperature is raised to 1300~1350 ℃, it is kept warm for 2~2.5 h; the infiltration sintering process is carried out in a nitrogen or hydrogen atmosphere, and the gas flow rate of the nitrogen or hydrogen is 50~80 sccm.

[0013] As a further solution of the present invention: in step S5, the pressure on the press is 8-10 t / cm 2 .

[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention innovatively proposes a method for preparing a molybdenum skeleton based on freeze-drying method, wherein molybdenum powder is fused with an organic solvent to form a slurry, and skeleton pores are formed by ice crystal growth under freezing conditions. Since its porosity and pore structure depend on ice crystal growth, it is a low-cost skeleton preparation method with controllable pores. While being easy to operate, it greatly saves the cost of skeleton preparation, making the industrial production of molybdenum skeletons with controllable pores possible, thereby promoting the industrial production of high-performance molybdenum-copper composite plates; 2. The present invention proposes a relatively stable slurry ratio, which can ensure that molybdenum particles rarely settle during the freezing process, thereby preparing a molybdenum skeleton with better performance. A small amount of copper powder is added to the slurry, which plays a role in inducing infiltration without affecting the stability of the slurry, increases the power of infiltration, makes the two phases of the molybdenum-copper composite material evenly distributed, and improves the density of the molybdenum-copper composite plate; 3. The pores of the molybdenum skeleton formed in the present invention are interconnected, which can ensure the continuous state of the infiltrated copper and effectively improve the conductivity of the molybdenum-copper composite plate. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The present invention is a process flow chart for preparing a molybdenum-copper composite plate based on a freeze-drying method; Figure 2 This is a schematic diagram of the structure of a freezing mold in preparing a molybdenum-copper composite plate based on a freeze-drying method according to the present invention; Figure 3 This is a metallographic structure diagram of the Mo50Cu50 composite plate prepared in Example 1 of the present invention; Figure 4 This is a metallographic structure diagram of the Mo60Cu40 composite plate prepared in Example 2 of the present invention; Figure 5 This is a metallographic structure diagram of the Mo70Cu30 composite plate prepared in Example 3 of the present invention; Figure 6 This is a metallographic structure diagram of the Mo80Cu20 composite plate prepared in Example 4 of the present invention; In the figure: 1. Insulated pipe body; 2. Cold transfer bottom plate. DETAILED DESCRIPTION

[0016] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] Example 1

[0018] Reference Figures 1 to 3 The method for preparing Mo50Cu50 composite sheet based on freeze drying method comprises the following steps: S1. Preparation of slurry: molybdenum powder, copper powder, sodium polyacrylate, xanthan gum and deionized water are mixed to obtain a mixed solution, wherein the solid content of molybdenum powder is 50 vol / %, the particle size of molybdenum powder is 5-10 μm, the solid content of copper powder is 35 vol / %, the particle size of copper powder is 3-5 μm, the concentration of sodium polyacrylate is 0.004 g / ml, and the concentration of xanthan gum is 0.004 g / ml; the mixed solution is stirred with a magnetic stirrer, the speed of the magnetic stirrer is 100 r / min, and the stirring time is 45 min to obtain a slurry precursor; the slurry precursor is then moved into a stainless steel ball mill, the diameter of the stainless steel ball mill is 2 mm, the ball-to-material ratio is 3:1, and a planetary ball mill is used for dispersion, the speed of the planetary ball mill is 200 r / min, and the dispersion time is 10 h to obtain the desired slurry, and the viscosity of the slurry is 4000 mPa·s; S2, preparation of a molybdenum skeleton, the slurry obtained in step S1 is moved into a freezing mold, the freezing mold comprises an insulating tube body 1 and a cold transfer bottom plate 2, the bottom of the insulating tube body 1 is fixedly connected to the cold transfer bottom plate 2, the height of the insulating tube body 1 is ≤ 1 mm, the insulating tube body 1 is made of acrylic insulating tube material, and the cold transfer bottom plate 2 is made of copper plate; the slurry is frozen and dried using a freeze dryer, the cooling temperature of the freeze dryer is -50 ° C, the cooling time is 3 h, the drying temperature is -15 ° C, and the drying time is 24 h, to obtain a molybdenum skeleton green body; then a vacuum tube furnace is used to debind and pre-sinter the molybdenum skeleton green body, the heating rate of the vacuum tube furnace is 5 ° C / min, and when the temperature is raised to 400 ° C, it is kept warm for 1 h; the debinding and pre-sintering processes are both carried out in a hydrogen atmosphere, and the gas flow rate of hydrogen is 50 sccm, to obtain a molybdenum skeleton; S3, preparation of copper block, using pure copper plate, cutting it, and cleaning and sandblasting its surface to obtain the required copper block, the copper infiltrated into the molybdenum skeleton of the copper block is called infiltration copper, the copper in the molybdenum-copper composite plate is composed of the copper added in step S1 and the infiltration copper, according to the content of the molybdenum powder and copper powder added in step S1, it can be obtained that the mass fraction of the molybdenum powder added in step S1 in the Mo50Cu50 composite plate is 50 wt / %, the mass fraction of the copper powder added in step S1 in the Mo50Cu50 composite plate is 30.5 wt / %, then the mass fraction of the infiltration copper in the Mo50Cu50 composite plate is 19.5 wt / %, according to the mass of the prepared Mo50Cu50 composite plate, the mass of the infiltration copper is calculated, and the mass of the copper block is 1.2 times the mass of the infiltration copper; S4, infiltration sintering, placing the molybdenum skeleton prepared in step S2 in a sintering mold, placing the copper block prepared in step S3 on the molybdenum skeleton, and performing infiltration sintering in a sintering furnace. The copper block infiltrates into the molybdenum skeleton by infiltration to obtain a molybdenum-copper composite plate. The heating rate of the sintering furnace is 5 ° C / min. When the temperature is raised to 1300 ° C, it is kept warm for 2 h. The infiltration sintering process is carried out in a nitrogen atmosphere with a nitrogen gas flow rate of 50 sccm. S5, post-processing, first milling the molybdenum-copper composite plate obtained in step S4 to remove excess copper on the surface, and then shaping it on a press with a pressure of 8 t / cm 2 , and finally grinding to form the final product.

[0019] The density of the prepared Mo50Cu50 composite plate is 98.3%, the hardness is 140.7 HV, the conductivity is 51.2IACS%, and the thermal conductivity is 237.6%. According to the metallographic structure diagram of the Mo50Cu50 composite plate, it can be seen that Mo and Cu are evenly distributed.

[0020] Example 2

[0021] Reference Figure 1 , Figure 2 and Figure 4 The method for preparing Mo60Cu40 composite sheet based on freeze drying method comprises the following steps: S1. Preparation of slurry: molybdenum powder, copper powder, sodium polyacrylate, xanthan gum and deionized water are mixed to obtain a mixed solution, wherein the solid content of molybdenum powder is 60 vol / %, the particle size of molybdenum powder is 5-10 μm, the solid content of copper powder is 25 vol / %, the particle size of copper powder is 3-5 μm, the concentration of sodium polyacrylate is 0.006 g / ml, and the concentration of xanthan gum is 0.006 g / ml; the mixed solution is stirred with a magnetic stirrer, the speed of the magnetic stirrer is 140 r / min, and the stirring time is 50 min to obtain a slurry precursor; the slurry precursor is then moved into a stainless steel ball mill, the diameter of the stainless steel ball mill is 3 mm, the ball-to-material ratio is 3:1, and a planetary ball mill is used for dispersion, the speed of the planetary ball mill is 240 r / min, and the dispersion time is 11 h to obtain the desired slurry, and the viscosity of the slurry is 4400 mPa·s; S2, preparation of a molybdenum skeleton, the slurry obtained in step S1 is moved into a freezing mold, the freezing mold comprises an insulating tube body 1 and a cold transfer bottom plate 2, the bottom of the insulating tube body 1 is fixedly connected to the cold transfer bottom plate 2, the height of the insulating tube body 1 is ≤ 1 mm, the insulating tube body 1 is made of acrylic insulating tube material, and the cold transfer bottom plate 2 is made of copper plate; the slurry is frozen and dried using a freeze dryer, the cooling temperature of the freeze dryer is -60 ° C, the cooling time is 3 h, the drying temperature is -15 ° C, and the drying time is 36 h, to obtain a molybdenum skeleton green body; then a vacuum tube furnace is used to debind and pre-sinter the molybdenum skeleton green body, the heating rate of the vacuum tube furnace is 6 ° C / min, and when the temperature is raised to 400 ° C, it is kept warm for 1 h; the debinding and pre-sintering processes are both carried out in a hydrogen atmosphere, and the gas flow rate of hydrogen is 50 sccm, to obtain a molybdenum skeleton; S3, preparation of copper block, using pure copper plate, cutting it, and cleaning and sandblasting its surface to obtain the required copper block, the copper infiltrated into the molybdenum skeleton of the copper block is called infiltration copper, the copper in the molybdenum-copper composite plate is composed of the copper added in step S1 and the infiltration copper, according to the content of the molybdenum powder and copper powder added in step S1, it can be obtained that the mass fraction of the molybdenum powder added in step S1 in the Mo60Cu40 composite plate is 60 wt / %, the mass fraction of the copper powder added in step S1 in the Mo60Cu40 composite plate is 21.8 wt / %, then the mass fraction of the infiltration copper in the Mo60Cu40 composite plate is 18.2 wt / %, according to the mass of the prepared Mo60Cu40 composite plate, the mass of the infiltration copper is calculated, and the mass of the copper block is 1.2 times the mass of the infiltration copper; S4, infiltration sintering, placing the molybdenum skeleton prepared in step S2 in a sintering mold, placing the copper block prepared in step S3 on the molybdenum skeleton, and performing infiltration sintering in a sintering furnace. The copper block infiltrates into the molybdenum skeleton by infiltration to obtain a molybdenum-copper composite plate. The heating rate of the sintering furnace is 6 ° C / min. When the temperature is raised to 1300 ° C, it is kept warm for 2 h. The infiltration sintering process is carried out in a nitrogen atmosphere with a nitrogen gas flow rate of 80 sccm. S5, post-processing, first milling the molybdenum-copper composite plate obtained in step S4 to remove excess copper on the surface, and then shaping it on a press with a pressure of 8 t / cm 2 , and finally grinding to form the final product.

[0022] The density of the prepared Mo60Cu40 composite plate is 98.7%, the hardness is 141.5 HV, the conductivity is 50.2IACS%, and the thermal conductivity is 235.2%. According to the metallographic structure diagram of the Mo60Cu40 composite plate, it can be seen that Mo and Cu are evenly distributed.

[0023] Example 3

[0024] Reference Figure 1 , Figure 2 and Figure 5 The method for preparing Mo70Cu30 composite sheet based on freeze drying method comprises the following steps: S1. Preparation of slurry: molybdenum powder, copper powder, sodium polyacrylate, xanthan gum and deionized water are mixed to obtain a mixed solution, wherein the solid content of molybdenum powder is 70 vol / %, the particle size of molybdenum powder is 5-10 μm, the solid content of copper powder is 15 vol / %, the particle size of copper powder is 3-5 μm, the concentration of sodium polyacrylate is 0.008 g / ml, and the concentration of xanthan gum is 0.008 g / ml; the mixed solution is stirred with a magnetic stirrer, the speed of the magnetic stirrer is 180 r / min, and the stirring time is 55 min to obtain a slurry precursor; the slurry precursor is then moved into a stainless steel ball mill, the diameter of the stainless steel ball mill is 4 mm, the ball-to-material ratio is 3:1, and a planetary ball mill is used for dispersion, the speed of the planetary ball mill is 280 r / min, and the dispersion time is 11 h to obtain the desired slurry, and the viscosity of the slurry is 4800 mPa·s; S2, preparation of a molybdenum skeleton, the slurry obtained in step S1 is moved into a freezing mold, the freezing mold comprises an insulating tube body 1 and a cold transfer bottom plate 2, the bottom of the insulating tube body 1 is fixedly connected to the cold transfer bottom plate 2, the height of the insulating tube body 1 is ≤ 1 mm, the insulating tube body 1 is made of acrylic insulating tube material, and the cold transfer bottom plate 2 is made of copper plate; the slurry is frozen and dried using a freeze dryer, the cooling temperature of the freeze dryer is -60 ° C, the cooling time is 4 h, the drying temperature is -20 ° C, and the drying time is 36 h, to obtain a molybdenum skeleton green body; then the molybdenum skeleton green body is debinded and pre-sintered using a vacuum tube furnace, the heating rate of the vacuum tube furnace is 6 ° C / min, and when the temperature is raised to 450 ° C, it is kept warm for 2 h; the debinding and pre-sintering processes are both carried out in a hydrogen atmosphere, and the gas flow rate of hydrogen is 80 sccm, to obtain a molybdenum skeleton; S3, preparation of copper block, using pure copper plate, cutting it, and cleaning and sandblasting its surface to obtain the required copper block, the copper infiltrated into the molybdenum skeleton of the copper block is called infiltration copper, the copper in the molybdenum-copper composite plate is composed of the copper added in step S1 and the infiltration copper, according to the content of the molybdenum powder and copper powder added in step S1, it can be obtained that the mass fraction of the molybdenum powder added in step S1 in the Mo70Cu30 composite plate is 70 wt / %, the mass fraction of the copper powder added in step S1 in the Mo70Cu30 composite plate is 13.1 wt / %, then the mass fraction of the infiltration copper in the Mo70Cu30 composite plate is 16.9 wt / %, according to the mass of the prepared Mo70Cu30 composite plate, the mass of the infiltration copper is calculated, and the mass of the copper block is 1.2 times the mass of the infiltration copper; S4, infiltration sintering, placing the molybdenum skeleton prepared in step S2 in a sintering mold, placing the copper block prepared in step S3 on the molybdenum skeleton, and performing infiltration sintering in a sintering furnace. The copper block infiltrates into the molybdenum skeleton by infiltration to obtain a molybdenum-copper composite plate. The heating rate of the sintering furnace is 6 ° C / min. When the temperature is raised to 1350 ° C, it is kept warm for 2.5 h. The infiltration sintering process is carried out in a hydrogen atmosphere with a hydrogen gas flow rate of 50 sccm. S5, post-processing, first milling the molybdenum-copper composite plate obtained in step S4 to remove excess copper on the surface, and then shaping it on a press with a pressure of 10 t / cm 2 , and finally grinding to form the final product.

[0025] The density of the prepared Mo70Cu30 composite plate is 98.0%, the hardness is 169.3 HV, the conductivity is 44.6IACS%, and the thermal conductivity is 218.5%. According to the metallographic structure diagram of the Mo70Cu30 composite plate, it can be seen that Mo and Cu are evenly distributed.

[0026] Example 4

[0027] Reference Figure 1 , Figure 2 and Figure 6 The method for preparing Mo80Cu20 composite sheet based on freeze drying method comprises the following steps: S1. Preparation of slurry: molybdenum powder, copper powder, sodium polyacrylate, xanthan gum and deionized water are mixed to obtain a mixed solution, wherein the solid content of molybdenum powder is 80 vol / %, the particle size of molybdenum powder is 5-10 μm, the solid content of copper powder is 5 vol / %, the particle size of copper powder is 3-5 μm, the concentration of sodium polyacrylate is 0.01 g / ml, and the concentration of xanthan gum is 0.012 g / ml; the mixed solution is stirred with a magnetic stirrer, the speed of the magnetic stirrer is 200 r / min, and the stirring time is 1 h to obtain a slurry precursor; the slurry precursor is then moved into a stainless steel ball mill, the diameter of the stainless steel ball mill is 5 mm, the ball-to-material ratio is 3:1, and a planetary ball mill is used for dispersion, the speed of the planetary ball mill is 300 r / min, and the dispersion time is 12 h to obtain the desired slurry, and the viscosity of the slurry is 5000 mPa·s; S2, preparation of a molybdenum skeleton, the slurry obtained in step S1 is moved into a freezing mold, the freezing mold comprises an insulating tube body 1 and a cold transfer bottom plate 2, the bottom of the insulating tube body 1 is fixedly connected to the cold transfer bottom plate 2, the height of the insulating tube body 1 is ≤ 1 mm, the insulating tube body 1 is made of acrylic insulating tube material, and the cold transfer bottom plate 2 is made of copper plate; the slurry is frozen and dried using a freeze dryer, the cooling temperature of the freeze dryer is -70 ° C, the cooling time is 4h, the drying temperature is -20 ° C, and the drying time is 48 h, to obtain a molybdenum skeleton green body; then the molybdenum skeleton green body is debinded and pre-sintered using a vacuum tube furnace, the heating rate of the vacuum tube furnace is 8 ° C / min, and when the temperature is raised to 450 ° C, it is kept warm for 2 h; the debinding and pre-sintering processes are both carried out in a hydrogen atmosphere, and the gas flow rate of hydrogen is 80 sccm, to obtain a molybdenum skeleton; S3, preparation of copper block, using pure copper plate, cutting it, and cleaning and sandblasting its surface to obtain the required copper block, the copper infiltrated into the molybdenum skeleton of the copper block is called infiltration copper, the copper in the molybdenum-copper composite plate is composed of the copper added in step S1 and the infiltration copper, according to the content of the molybdenum powder and copper powder added in step S1, it can be obtained that the mass fraction of the molybdenum powder added in step S1 in the Mo80Cu20 composite plate is 80 wt / %, the mass fraction of the copper powder added in step S1 in the Mo80Cu20 composite plate is 4.4 wt / %, then the mass fraction of the infiltration copper in the Mo80Cu20 composite plate is 15.6 wt / %, according to the mass of the prepared Mo80Cu20 composite plate, the mass of the infiltration copper is calculated, and the mass of the copper block is 1.2 times the mass of the infiltration copper; S4, infiltration sintering, placing the molybdenum skeleton prepared in step S2 in a sintering mold, placing the copper block prepared in step S3 on the molybdenum skeleton, and performing infiltration sintering in a sintering furnace. The copper block infiltrates into the molybdenum skeleton by infiltration to obtain a molybdenum-copper composite plate. The heating rate of the sintering furnace is 8 ° C / min. When the temperature is raised to 1350 ° C, it is kept warm for 2.5 h. The infiltration sintering process is carried out in a hydrogen atmosphere with a hydrogen gas flow rate of 80 sccm. S5, post-processing, first milling the molybdenum-copper composite plate obtained in step S4 to remove excess copper on the surface, and then shaping it on a press with a pressure of 10 t / cm 2 , and finally grinding to form the final product.

[0028] The density of the prepared Mo80Cu20 composite plate is 97.5%, the hardness is 181.5 HV, the conductivity is 32.1IACS%, and the thermal conductivity is 198.4%. According to the metallographic structure diagram of the Mo80Cu20 composite plate, it can be seen that Mo and Cu are evenly distributed, and the molybdenum powder and copper powder are evenly distributed.

[0029] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a molybdenum-copper composite sheet based on a freeze-drying method, characterized in that: The steps include: S1. Preparation of slurry: mixing a dispersant, a binder, molybdenum powder, copper powder and deionized water to obtain a mixed solution; stirring the mixed solution with a magnetic stirrer to obtain a slurry precursor; then transferring the slurry precursor into a stainless steel ball mill, and dispersing it with a planetary ball mill to obtain the desired slurry; S2, preparation of a molybdenum skeleton, transferring the slurry obtained in step S1 into a freezing mold, freezing and drying the slurry using a freeze dryer to obtain a molybdenum skeleton green body; and then debinding and pre-sintering the molybdenum skeleton green body using a vacuum tube furnace to obtain a molybdenum skeleton; S3, preparation of copper block, using pure copper plate, cutting it, and cleaning and sandblasting its surface to obtain the required copper block; S4, infiltration sintering, placing the molybdenum skeleton prepared in step S2 in a sintering mold, placing the copper block prepared in step S3 on the molybdenum skeleton, and performing infiltration sintering in a sintering furnace, wherein the copper block infiltrates into the molybdenum skeleton through infiltration to obtain a molybdenum-copper composite plate; S5, post-processing, firstly, the molybdenum-copper composite plate obtained in step S4 is milled to remove the excess copper on the surface, then shaped on a press, and finally ground to form a final product.

2. The method for preparing a molybdenum-copper composite sheet based on freeze-drying method according to claim 1, characterized in that: In step S1, the solid content of molybdenum powder in the slurry is 50-80 vol%, the solid content of copper powder is 5-35 vol%, the particle size of the molybdenum powder is 5-10 μm, and the particle size of the copper powder is 3-5 μm; the dispersant is sodium polyacrylate, and the concentration of the sodium polyacrylate is 0.004-0.01 g / ml; the binder is xanthan gum, and the concentration of the xanthan gum is 0.004-0.012 g / ml.

3. The method for preparing a molybdenum-copper composite sheet based on freeze-drying method according to claim 2, characterized in that: In step S1, the rotation speed of the magnetic stirrer is 100-200 r / min, and the stirring time is 45 min-1 h; the diameter of the stainless steel ball mill is 2-5 mm, and the ball-to-material ratio is 3:1; the rotation speed of the planetary ball mill is 200-300 r / min, and the dispersion time is 10-12 h. The viscosity of the obtained slurry is 4000-5000 mPa·s.

4. The method for preparing a molybdenum-copper composite sheet based on freeze-drying method according to claim 3, characterized in that: In step S2, the freezing mold includes an insulating tube body (1) and a cold transfer bottom plate (2), the bottom of the insulating tube body (1) is fixedly connected to the cold transfer bottom plate (2), the height of the insulating tube body (1) is ≤ 1 mm, the insulating tube body (1) is made of acrylic insulating tube material, and the cold transfer bottom plate (2) is made of copper plate.

5. The method for preparing a molybdenum-copper composite sheet based on freeze-drying method according to claim 4, characterized in that: In step S2, the cooling temperature of the freeze dryer is -50 ~ -70 ° C, the cooling time is 3 ~ 4 h, the drying temperature is -15 ~ -20 ° C, and the drying time is 24 ~ 48 h; the heating rate of the vacuum tube furnace is 5 ~ 8 ° C / min, and when the temperature is increased to 400 ~ 450 ° C, it is kept warm for 1 ~ 2 h; the debinding and pre-sintering processes are both carried out in a hydrogen atmosphere, and the gas flow rate of the hydrogen is 50 ~ 80 sccm.

6. The method for preparing a molybdenum-copper composite sheet based on freeze-drying method according to claim 5, characterized in that: The copper infiltrated into the molybdenum skeleton by the copper block is called infiltration copper. The copper in the molybdenum-copper composite plate is composed of the copper added in step S1 and the infiltration copper. The mass fraction of the infiltration copper is w 铜2 =100%-w 钼 -w 铜1 , where w 钼 is the mass fraction of the molybdenum powder added in step S1 in the molybdenum-copper composite plate, w 铜1 is the mass fraction of the copper powder added in step S1 in the molybdenum-copper composite plate. The mass of the infiltrated copper is calculated according to the mass of the prepared molybdenum-copper composite plate. In step S3, the mass of the copper block is 1.2 times the mass of the infiltrated copper.

7. The method for preparing a molybdenum-copper composite sheet based on freeze-drying method according to claim 6, characterized in that: In step S4, the sintering mold is made of graphite or corundum, the heating rate of the sintering furnace is 5-8 °C / min, and when the temperature is raised to 1300-1350 °C, it is kept warm for 2-2.5 h; the infiltration sintering process is carried out in a nitrogen or hydrogen atmosphere, and the gas flow rate of the nitrogen or hydrogen is 50-80 sccm.

8. The method for preparing a molybdenum-copper composite sheet material based on freeze-drying method according to claim 7, characterized in that: In step S5, the pressure on the press is 8-10 t / cm 2 .

Citation Information

Patent Citations

  • A method for preparing Cu-MoCu-Cu composite plates

    CN102284701A

  • Nano-iron-powder doped copper-tungsten alloy and preparation method thereof

    CN106148794A

  • Porous material with continuous porosity gradient and preparation method of porous material

    CN107200583A

  • Porous flaky molybdenum phosphide / carbon composite material and preparation method thereof

    CN110479332A

  • Preparation method of molybdenum-copper alloy for electronic packaging

    CN115418517A

Cited By

  • Preparation method of molybdenum-copper heat sink material

    CN120001987A